The Influence of Cildren’s Gadget Use on Mother-Child Communication Patterns: A Comparative Study Between Working and Non-Working Mothers in Parepare City - Andi Weyana Nurul; A. Octamaya Tenri Awaru; Ridwan Said Ahmad; Najamuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aimed to analyze if there is a significant influence between children's gadget use on mother and child communication patterns, The differences in the influence of children's gadget use on mother-child communication patterns between families of working mothers and families of non-working mothers, a significant difference in the level of children's gadget use on communication patterns between children whose mothers work and those who do not work in Parepare City. This research uses a comparative quantitative approach by determining the sample using the Slovin margin formula of 100 people, including 57 working mothers and 43 non-working mothers. Data collection techniques used questionnaires in google forms and documentation, while data analysis was carried out using descriptive and inferential statistical techniques using the SPSS program. The results of this research showed that there is a positive and significant influence between children's gadget use on mother and child communication patterns with a significance value (Sig.) = 0.002 and a positive regression coefficient (B = 0.190). Mother's employment status moderates this relationship with the Sig value. interaction = 0.041, meaning that the influence of gadget use on communication is stronger in the families of working mothers compared to non-working mothers and there is a significant difference in the level of children's gadget use between working and non-working mothers (Sig. = 0.000), but there is no significant difference in the communication patterns of mothers and children (Sig. = 0.618). The conclusion of this research was the mother's employment status moderates this relationship with the Sig value. interaction = 0.041, meaning that the influence of gadget use on communication is stronger in families of working mothers than non-working mothers and children of working mothers have a higher level of gadget use than children of non-working mothers.